Calcogenetos e calcogenolatos (Se, Te) de paládio: síntese e caracterização estrutural - Cechin, Camila Nunes (2020)
This work describes the synthesis and characterization of eleven new palladium compounds with formula [Pd3(-SeMes)4(bipy)2](PF6)2·2MeCN (1), [Pd3(-SePh)4(bipy)2](PF6)2·bipy (2), [Pd2(- SePh)2(bipy)2](PF6)2 (3), [Pd2(-SeC6H4Cl-p)2(bipy)2](PF6)2 (4), [Pd3(3-Se)2(bipy)3](PF6)2∙5THF (5), [Pd2(-SeC6H4F-p)2(bipy)2](PF6)2 (6), [Pd3(-TeMes)4(bipy)2](PF6)2 (7), [Pd2(-TePh)2(bipy)2](PF6)2 (8), [Pd2(-TeC6H4 tBu-p)2(bipy)2](PF6)2∙DMF (9), [Pd2(-TeC6H4F-p)2(bipy)2](PF6)2 (10) e [PdI(TePyo)( I2TePy-o)2] (11), based on diaryldichalcogenides containing electron donating (EDG) or electron withdrawing groups (EWG). Compounds 1 – 10 have intramolecular Pd∙∙∙Pd interactions which vary according to the structural conformation promoted by different (EAr)2 used. Only compound 9 has intermolecular Pd∙∙∙Pd interactions, which are shorter when compared to its intramolecular Pd ∙∙∙ Pd. Six of these compounds derive from selenium and five of these derive from tellurium and all of it were characterized by X ray diffraction, besides elemental analysis, infrared spectroscopy, mass spectrometry and nuclear magnetic resonance spectroscopy 77Se, 125Te (NMR). The methodologies used to get compounds 1 – 11 were basically oxidative addition (1, 5, 7, 8, 9 e 10) and ligand substitution (2, 3, 4 e 6). On the other hand, compound 11 was obtained through elemental palladium oxidation by a diiodine adduct of (o-PyTe)2 generated in situ during the reaction. The use of (ArE)2 containing EDG and EWG resulted in structures with different nuclearities, conformations and nuclearities, conformations and coordination environments. The generated equilibrium in solution for compound 3 was determined by 1H, 13C and 77Se, where the 2D spectra (COSY, HSQC and HMBC) were carried out to assign proton and carbon signals corresponding to its chemical shifts from the structures in equilibrium. The mass spectrum for compound 3 shows the signals related to the fragments of the two species in equilibrium (3 and 3 'determined by NMR), confirming the NMR data interpreted. DFT calculations were carried out for compound 11 and the results suggest delocalized electrons (aromaticity) in its five-membered rings. These delocalized electrons in the system homogenize the oxidation states of the different tellurium species, [I2TePy-o]- and [TePy-o]+, in the structure of 11.